The Optimization of Porang starch-lactose as a co-processed excipient of Bajakah (Spatholobus littoralis Hassk) root dried extract's effervescent tablet - Ermawati, Dian Eka; Andini, Bimar Putri; Damayanti, Avina Kusuma (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Bajakah root has stronger antioxidant activity than vitamin C. The Dayak people use it to maintain health. Bajakah root infusion has an unpleasant taste and aroma, also unstable, so effervescent tablets are developed to resolve that problem. Effervescent tablets are prepared by direct compression method. The starch of porang tuber is a food that can act as fillers and tablet binders. The co-processed excipient can produce tablet fillers for the directly compressed method. Co-processed excipients of lactose-porang starch have excellent flow properties, improve tablet hardness, have good compatibility, and are cheaper. In this study, the proportions of porang starch and lactose as co-processed excipients were determined using the Simplex Lattice Design method, and then tested the flow properties and granule repose angle. The physical properties of the tablets include weight uniformity, hardness, brittleness, dissolution time, and antioxidant activity test. Test data were analyzed using the One Sample T-test. The results showed that effervescent tablets with co-processed excipient porang starch-lactose 64: 36% provide good physical stability, granule flow time of 10.45 ± 0.29 gram/second, granule repose angle of 27.52 ± 0.95°; tablet weight uniformity with a CV value of 1.021%; tablet hardness 5.74 ± 0.07 Kg, tablet friability of 0.549 ± 0.03%; tablet disintegration time 86 ± 4 seconds. The bajakah root has antioxidant activity of 0.155 mg/mL.